Niṣāb of Zakāt : An Analysis of Gold-Based Benchmark and the Macroeconomic Factors on Zakāt Collection - SENAWI, AZHAN RASHID (2018)
Zakāt collection determines the zakāt distribution. Thus, a higher zakāt collection leads to a huge benefit to the zakāt recipients. However, there is a constraint in terms of its collection due to the external factors that undeniably could affect the collection especially from the effect of the macroeconomic factors. It becomes critical when the price of gold (one of the macroeconomic commodities and used as a niṣāb benchmark for zakāt in Malaysia) claimed to have a negative influence on the collection of zakāt as well as distribution of the zakāt to the poor.